Effect of the Type of Cover and Planting Media on the Growth of Kepok Banana (Musa paradisiaca L.) During the Acclimatization Period - Elan Hardiansyah; Muhammad Idris; Khairunnisa Khairunnisa (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
According to the Indonesian Central Statistics Agency (BPS), banana production has consistently increased from 2020 to 2023, around 12.97%. Unfortunately, Indonesia's annual banana production is still fluctuating and difficult. This is due to the difficulty of obtaining superior seeds in large quantities in a short time. The aim of this research is to determine the effect of the type of cover and planting media on the vegetative growth of kepok banana (Musa Paradisiaca L.) during the acclimation period. This research uses a Divided Plot Design (RPT), the cover as the main plot and the planting medium as the sub-plot. The type of hood used is 16% UV plastic and 75% paranet while the planting media used is top soil + cocopeat, top soil + burnt husk and top soil + vermicompost (vermicompost) in a ratio of 1:2. Data analysis used one way ANOVA and continued with the Duncan test. The results obtained included that the hood treatment had a significant effect on the percentage of live seeds, plant length, stem diameter, leaf area and total chlorophyll. The 16% UV plastic cover type produces the best average results compared to 75% paranet. Planting media had a significant effect on leaf area and total chlorophyll and had no significant effect on other parameters. The interaction between the combination of cover and planting media is found in the parametersof leaf area and total chlorophyll.